Eksplorasi Etnomatematika Pada Gerakan Tari Serimpi Sebagai Sumber Belajar Matematika Pada Materi Geometri - Condro Endang Werdiningsih; Sudiyah Anawati; Roida Eva Flora Siagian (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to demonstrate mathematical concepts as an activity. The research method used in this study is a qualitative descriptive research method with an ethnographic approach. The exploratory qualitative approach is an empirical and theoretical approach that aims to obtain in-depth descriptions and analyses of culture based on fieldwork. Data collection techniques used are observation, interviews, field notes, and documentation. Based on the research conducted, geometric elements were found in the Serimpi dance movements and their floor patterns and dance movements, including two-dimensional geometry, angular geometry, and transformation geometry. Exploration of Ethnomathematics in Dance Movements, the position of the dancer's hands, feet, and body.